2023
DOI: 10.3390/app132413224
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Range-Searching Initial Orbit-Determination Method and Correlation of Optical Observations for Space Debris

Xiangxu Lei,
Shengfu Xia,
Hongkang Liu
et al.

Abstract: The Changchun Observatory of the National Astronomical Observatories, Chinese Academy of Sciences, and the Shanghai Astronomical Observatory are used to generate very short arc (VSA) angle observations of objects in low Earth orbit (LEO) and geostationary orbit (GEO) with their ground-based electrical–optical telescope arrays (EA), the Changchun EA and SAO FocusGEO, respectively. These observations are used in this paper. The range-searching (RS) algorithm for initial orbit determination (IOD) is improved thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Observations can be performed both from large ground facilities and via distributed in-orbit systems. In [5], the authors provide an improved method for determining the orbital parameters of space objects obtained via very short arc observations from a ground telescope; it is shown that this method has a high success rate and can be employed for the rapid assessment of fragmentation events. With respect to in situ observation, in [6], a model for designing and assessing the efficiency of a constellation for space debris observation is presented; through long-term continuous observation, these constellations could maintain an orbit catalogue of the majority of the objects in LEO, and they could also provide up-to-date information for space situational awareness.…”
mentioning
confidence: 99%
“…Observations can be performed both from large ground facilities and via distributed in-orbit systems. In [5], the authors provide an improved method for determining the orbital parameters of space objects obtained via very short arc observations from a ground telescope; it is shown that this method has a high success rate and can be employed for the rapid assessment of fragmentation events. With respect to in situ observation, in [6], a model for designing and assessing the efficiency of a constellation for space debris observation is presented; through long-term continuous observation, these constellations could maintain an orbit catalogue of the majority of the objects in LEO, and they could also provide up-to-date information for space situational awareness.…”
mentioning
confidence: 99%